2018
DOI: 10.1111/apt.14937
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: risk of hepatocellular carcinoma in non‐alcoholic steatohepatitis without cirrhosis compared to other liver diseases

Abstract: In non-cirrhotic subjects, those with NASH have a higher risk of HCC compared to other aetiologies of liver disease. Further study investigating the risk factors of HCC among non-cirrhotic NASH patients is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
211
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(222 citation statements)
references
References 54 publications
5
211
0
6
Order By: Relevance
“…When considering a screening test, once must consider the benefits and harms, including the false positive impact . We did not perform a cost‐efficiency analysis, but the simple analysis of the number needed to screen, and the negative predictive value suggested that the surveillance of patients without cirrhosis by the algorithm combining LCR1 and LCR2 could be compared to the standard including only cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…When considering a screening test, once must consider the benefits and harms, including the false positive impact . We did not perform a cost‐efficiency analysis, but the simple analysis of the number needed to screen, and the negative predictive value suggested that the surveillance of patients without cirrhosis by the algorithm combining LCR1 and LCR2 could be compared to the standard including only cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…While most HCC occur on a background of cirrhosis, NASH‐associated HCC can develop either in the presence or absence of cirrhosis. Indeed, this study by Stine et al joins a solid body of literature indicating that patients with pre‐cirrhotic NASH are at increased risk of HCC, and that the various components of the metabolic syndrome may each contribute to the overall risk. This most recent article reports the results of two individual meta‐analyses comprising 19 separate studies with a combined patient pool of 168 571 .…”
mentioning
confidence: 72%
“…The first finding was of a significantly increased prevalence of HCC in NASH patients over non‐NASH patients (22.5% vs 13.6%) . The second, more striking, observation was that non‐cirrhotic NASH patients had a near three‐fold increased risk of HCC compared to non‐cirrhotic patients with other forms of liver disease . As the authors concede, there are inherent limitations to the study: missing data, heterogeneity among included studies (eg, differences in how NASH was defined, including variations in alcohol consumption thresholds applied, limited information on disease stage in non‐cirrhotic cases), and the potential for reporting bias within the primary literature may all have influenced the findings.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…However, the link between fibrosis and carcinogenesis appears to be less definitive in patients with NASH, as a sizeable proportion of NASH patients with HCC do not have significant underlying fibrosis. Several case reports and case series have pointed out this phenomenon of HCC arising in noncirrhotic NASH, and a recent meta‐analysis of 19 studies has shown that the prevalence of HCC in noncirrhotic NASH was up to 38.0% . The mechanisms that contribute to the development of HCC in obesity in the absence of NASH and/or overt fibrosis or cirrhosis have remained unexplored.…”
mentioning
confidence: 99%